Disasters, Drought, Poverty and Injustice as Root of Conflict Causes in Sudan - Elsiddiq Elsunna (GoAcademica Research & Publishing, 2020)
This study aims to analyze gender equality in the promotion of structural positions in the Government of West Java Province. This research design uses qualitative methods with data collection techniques in the form of in-depth interviews and documentation studies. While the research analysis technique is done by data reduction, data presentation, and conclusion drawing. The results of the study concluded that gender equality in the promotion of structural positions in West Java Province had not been realized optimally because the competency, qualifications, and work behavior of female civil servants are considered lower than men. Various servants faced by female civil servants for good promotion internal factors, namely the dual role and lack of motivation of women to progress, also obstacles to external factors stemming from the family, community, and organizational culture that are not gendered responsive. In addition to competence, qualifications, and work behavior, other considerations were found for the promotion of the position of a female civil servant, namely: multiple roles, type of work and location of assignments; this made women less likely to get strategic position promotions.